Porn chic : exploring the contours of raunch eroticism - Lynch, Annette (Annette Ferne) (Dress, body, culture., 2012)
The mainstreaming of pornographic imagery into fashion and popular culture at the turn of the millennium in Britain and the US signalled a dramatic cultural shift in construction of both femininity and masculinity. For men and women, raunch became the new cool. This engaging book draws from a diverse range of examples including film, popular tabloids, campus culture, mass media marketing campaigns, facebook profiles, and art exhibits to explore expressions and meanings of porn chic. Bringing a cultural and feminist lens to the material, this book challenges the reader to question the sexual ag.